On the origin of the strain hardening mechanisms of Ni20Cr alloy manufactured by laser powder bed fusion. (June 2023) - Joshi, Shubham Sanjay; Keller, Clément; Mas, Lydie; Lefebvre, Williams; Hug, Eric; Couzinie, Jean-Philippe
Highlights: LPBF Ni20Cr alloy is employed to investigate strain mechanisms. Tensile tests, dislocation observations and analytical modeling is performed. Dendrites associated to LPBF are responsible for about 43% of the yield stress. Strain hardening is controled by dendrites in LPBF Ni20Cr alloy. Abstract: Additively Manufactured (AM) metallic alloys differ from their conventionally produced counterparts by complex multi-scaled microstructures leading to deeply modified mechanical behavior. The characterization of these new links between microstructure and mechanical properties is of first importance. Nevertheless, many alloys produced by Laser Powder Bed Fusion (LPBF) process exhibit multi-phase microstructures which makes difficult the understanding of these links. In this article, we aimed at simplifying this complexity by investigating the basic strain hardening mechanisms of AM (LPBF) alloys of a theoretically monophasic Ni20Cr alloy manufactured by laser powder bed fusion. Based on the analysis of the microstructure and the tensile mechanical behavior including loading-unloading-relaxation tests, a comparison with conventionally manufactured Ni20Cr alloy is performed. First, an increase in yield stress for the LPBF samples is observed due to both effective stress and backstress modification. Second, the strain hardening mechanisms are modified for LPBF manufactured samples compared to cast ones. Kocks-Mecking model is then employed to reproduce the tensile curves and better analyze the strain hardening mechanisms. Results are discussed in terms of specific LPBF microstructure feature contributions to stress and strain hardening. We reveal that dislocation cells associated to dendrites are proved to be responsible for about 50% of the improved yield stress of LPBF material and seem to control the dislocation production, forest interactions being inoperative for those materials.